Output Growth, Total Factor Productivity, and Technical Efficiency in Nepalese Manufacturing Industries - Regmi, Udaya Raj (Economic Journal of Nepal, 2006)
This paper seeks to identify the sources of output growth as well as total factor productivity in the manufacturing industries in Nepal over the period 1981/82-2001/02, employing Divisia Tornquist approximation and production frontier models respectively. Capital and material inputs are found to be the most important sources of output growth whereas labor input has negligible contribution to output growth in the manufacturing industries in Nepal. The TFP growth is negative in almost all the industries due to the technical inefficiency coupled with low level of technological progress. Economic Journal of Nepal Vol.29(2) 2006 pp.85-92